2021
DOI: 10.1002/acp.3851
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards feminism predict susceptibility to feminism‐related fake news

Abstract: Summary False memories may be especially likely when one is exposed to misinformation that is consistent with one's beliefs. Here, we assessed whether feminist attitudes predict susceptibility to feminism‐related fake news. In Experiment 1 (n = 1537), the more negative participants' attitudes towards feminism, the more likely they were to report a false memory for a fabricated event that negatively reflected on the feminist movement, and vice‐versa. This effect was only evident for those who interpreted the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
3
7
0
2
Order By: Relevance
“…The findings can also be explained via fuzzy trace theory, if the gist of the fake news story overlaps with other related memories. These results are in line with previous studies which have linked attitudinal congruence with the formation of false memories for fake news about an abortion referendum (Murphy et al, 2019 ), the feminist movement (Murphy et al, 2021 ) and US politics (Frenda et al, 2013 ). Experiment 1 dealt exclusively with fabricated stories about events that never took place.…”
Section: Experiments 1 Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings can also be explained via fuzzy trace theory, if the gist of the fake news story overlaps with other related memories. These results are in line with previous studies which have linked attitudinal congruence with the formation of false memories for fake news about an abortion referendum (Murphy et al, 2019 ), the feminist movement (Murphy et al, 2021 ) and US politics (Frenda et al, 2013 ). Experiment 1 dealt exclusively with fabricated stories about events that never took place.…”
Section: Experiments 1 Discussionsupporting
confidence: 92%
“…The current research adds to literature suggesting that congruence of a news item with pre-existing beliefs may be a significant contributing factor to false memory formation (Frenda et al, 2013;Murphy et al, 2019Murphy et al, , 2021. This paper builds on recent research which has examined the influence of congruency on simple item-pairing paradigms (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Research has demonstrated that individuals can form false memories when exposed to fabricated news stories (Frenda et al, 2013;, often reporting that they remembered the event happening and had seen the story in the media (Murphy et al, 2019). False memories are more likely in this paradigm when the information presented is in line with current attitudes (Calvillo et al, 2023;Frenda et al, 2013;Greene, de Saint Laurent, et al, 2022;Greene, Levine, et al, 2022;Murphy et al, 2021), consistent with the source monitoring framework (Johnson et al, 1993).…”
Section: False Memories For Fake Newsmentioning
confidence: 78%